Employment and Other Income Sources among Homeless Youth - Slesnick, Natasha (J Prim Prev, 2018)
Homeless youth report high rates of unemployment. While homeless serving agencies usually offer employment services, most homeless youth are disengaged from homeless service agencies, and a limited number of studies have examined employment and other income sources among service disconnected youth. Our study examined income sources and change in income among service disconnected youth, all of whom received Strengths-Based Outreach and Advocacy (SBOA, N = 79). Findings revealed that over time employment and legal income from non-survival behaviors increased (e.g., governmental assistance and receiving income from friends and relatives), while income from survival behaviors decreased (e.g., prostitution, stealing, selling possessions, selling blood or plasma). Although unemployment among these youth remained high (62%), income from survival behaviors reduced most drastically. Findings also suggest that employment is linked to housing stability and mental health, as is substance use and income, which suggests that mental health, housing, and substance use treatment services are important components in income stabilization for homeless youth.